Global challenges of implementing human papillomavirus vaccines - Mishra Amrita; Graham Janice E (BMC, 2011)
Abstract Human Papillomavirus vaccines are widely hailed as a sweeping pharmaceutical innovation for the universal benefit of all women. The implementation of the vaccines, however, is far from universal or equitable. Socio-economically marginalized women in emerging and developing, and many advanced economies alike, suffer a disproportionately large burden of cervical cancer. Despite the marketing of Human Papillomavirus vaccines as the solution to cervical cancer, the market authorization (licensing) of the vaccines has not translated into universal equitable access. Vaccine implementation for vulnerable girls and women faces multiple barriers that include high vaccine costs, inadequate delivery infrastructure, and lack of community engagement to generate awareness about cervical cancer and early screening tools. For Human Papillomavirus vaccines to work as a public health solution, the quality-assured delivery of cheaper vaccines must be integrated with strengthened capacity for community-based health education and screening.